2018
DOI: 10.1155/2018/2860213
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Recycled Asphalt Pavement Material on Permeability and Bearing Capacity in the Base Layer

Abstract: e purpose of this research was to investigate the effects of recycled asphalt pavement (RAP) and cement content on the permeability and bearing capacity characteristics of aggregate base courses. Mixtures containing untreated RAP ranging between 0 and 100 percent and 1, 2, and 3% cement-treated RAP were subjected to laboratory tests (bitumen content, sieve analysis, modified proctor, soaked California bearing ratio (CBR), and constant-level permeability tests). e results showed that, as the RAP percentage in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 9 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…When the quantity of RAP in the recycled hot bituminous mix is 20% or less, the viscosity grade of bitumen should be the same as specified in Table 1. If the quantity of RAP in the mixture ranges from 20 to 35% (Seferoğlu et al, 2018). The viscosity grade of the virgin bitumen should be one grade softer than the grade generally specified for a 100% virgin mix.…”
Section: Bitumenmentioning
confidence: 99%
“…When the quantity of RAP in the recycled hot bituminous mix is 20% or less, the viscosity grade of bitumen should be the same as specified in Table 1. If the quantity of RAP in the mixture ranges from 20 to 35% (Seferoğlu et al, 2018). The viscosity grade of the virgin bitumen should be one grade softer than the grade generally specified for a 100% virgin mix.…”
Section: Bitumenmentioning
confidence: 99%
“…However, in previous analysis, the quantitative measurements in microscale moisture distribution within samples were difficult to perform. That hindered the discussions on the macroscale permeability [2,[32][33][34][35]. The micro-scale seepage characteristics, mainly include local seepage velocity and wetting front position.…”
Section: X-ray Scanning and Seepage Characteristic Determinationmentioning
confidence: 99%
“…A correlation equation is observed between PI and MBV, as shown in (3). Witczak et al [22,23] suggested subjective criteria for goodness predictions based on the coefficient of determination (R 2 ) values. An excellent fit can be defined as R 2 ≥ 0.9, a good fit covers the R 2 range of 0.7-0.89, and a fair fit is defined as 0.4 ≤ R 2 ≤ 0.69. erefore, (3) is a good fit for selected cohesive soils and can provide a relatively satisfactory correlation.…”
Section: Correlations Between Mbv and Pi And Between P 200 And Mbvmentioning
confidence: 99%